PEMETAAN KAPASITAS PONDOK PESANTREN DI KABUPATEN BUOL DAN TOLI-TOLI SULAWESI TENGAH - Badruzzaman Badruzzaman (Balai Penelitian dan Pengembangan Agama Makassar, 2018)
The Ministry of Religion Republic of Indonesia has issued a Decree on IslamicReligious Education which regulates the management of Pondok Pesantren.However, it has not been maximally implemented in various regions. This studyaims to map the capacity of pesantren components according to the regulation.The deskrif study of this survey found that there was still a diversity ofcapacitation in Pondok Pesantren. This diversity was found in the existence,qualifications and compotency of the kiai, santri who live in pondok, huts andfacilities, mosques, the program of “kitab kuning“ learning, the types of „kitabkuning taught, and learning to defend the country. This study recommends thatthe management of pondok pesantren be maneuvered; rearrange the form ofpesantren according to the regulations of religious education that has beenpublished; and policies to increase the capacity of pesantren should beincreased